Hyaluronic acid (HA)-Gd(III) and HA-Fe(III) microgels as MRI contrast enhancing agents. (1st February 2022) - Sahiner, Nurettin; Umut, Evrim; Suner, Selin S.; Sahiner, Mehtap; Culha, Mustafa; Ayyala, Ramesh S.
Abstract: Hyaluronic acid (HA) was crosslinked with Gd(III) and Fe(III) ions rendering physically crosslinked HA-metal(III) microgels as magnetic resonance imaging (MRI) enhancing contrast agents. These HA-Gd(III) and HA-Fe(III) microgels are injectable with size range, 50–5000 nm in water. The same isoelectric point, pH 1.2 ± 0.1, was measured for both microgels. HA-Gd(III) and HA-Fe(III) microgels are hemo-compatible biomaterials and can be safely used in intravascular applications up to 1000 μg/mL concentration. Furthermore, no significant toxicity was attained as 95 ± 8 and 81 ± 2% cell viability on L929 fibroblast cells at 100 μg/mL of HA-Gd(III) and HA-Fe(III) microgels were measured. Moreover, HA-Gd(III) microgels were found to afford significant contrast improvement capability in MRI with proton relaxivity, r1  = 2.11 mM −1  s −1, comparable with the values reported for Gd(III) labeled functionalized HA gel systems and commercial Gd based contrast agents. Graphical abstract: Unlabelled Image Highlights: Physically crosslinked HA-M(III) microgels are intravascularly injectable safe materials. Hemocompatible HA-Gd(III) and HA-Fe(III) microgels as MRI signal enhancer are prepared. HA-M(III) microgels provide promising potential in Alzheimer treatment as Fe(II) chelator. HA-Gd(III) and HA-Fe(III) microgels as natural biocompatible and blood compatible carriers